Social Reference Points and Risk Taking - Frederik Schwerter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We test whether social reference points impact individual risk taking. In a laboratory experiment, decision makers observe the earnings of a peer subject before making a risky choice. We exogenously manipulate the peer earnings across two treatments. We find a significant treatment effect on risk taking: decision makers vary their risk taking in order to surpass or stay ahead of their peer. Our findings are consistent with a social-comparison-based, reference-dependent preference model that formalizes relative concerns via social loss aversion. Additionally, we relate our findings to the impact of private reference points on risk taking.
Keywords: C91; D03; D81; 330